Tinjauan Yuridis Terhadap Perlindungan Hak Asasi Manusia Pada Pencari Suaka (Asylum Seeker) - Fadlu, Muhammad; Intania Nurul Apriliani Putri (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
Human rights issues are humanitarian issues in international scope, and almost all countries experience these problems, including Indonesia. Asylum seekers are closely related to humanitarian law and human rights.  Because in reality, asylum seekers are people whose human rights have been violated by their own country.  Due to the large number of asylum seekers living in Indonesia, Indonesia has more or less had to deal with this problem.  Indonesia has issued several regulations regarding the problem of asylum seekers. This shows how serious Indonesia is in responding to the problem of asylum seekers.